2022
DOI: 10.3390/genes13040618
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure Analysis and Association Mapping for Turcicum Leaf Blight Resistance in Tropical Maize Using SSR Markers

Abstract: Maize is an important cereal crop in the world for feed, food, fodder, and raw materials of industries. Turcicum leaf blight (TLB) is a major foliar disease that can cause more than 50% yield losses in maize. Considering this, the molecular diversity, population structure, and genome-wide association study (GWAS) for TLB resistance were studied in 288 diverse inbred lines genotyped using 89 polymorphic simple sequence repeats (SSR) markers. These lines werescreened for TLB disease at two hot-spot locations und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…When assessing the genetic diversity in maize genotypes, SSR remains the preferred choice due to their co-dominant and multi-allelic nature, abundance, and loci specificity [23]. In the current study, 748 alleles with a range of 2 to 8 per locus were identified among 310 maize inbred lines using 186 polymorphic SSRs (Table S1).…”
Section: Germplasms Diversity and Multiple Insect-resistance Evaluationmentioning
confidence: 98%
See 1 more Smart Citation
“…When assessing the genetic diversity in maize genotypes, SSR remains the preferred choice due to their co-dominant and multi-allelic nature, abundance, and loci specificity [23]. In the current study, 748 alleles with a range of 2 to 8 per locus were identified among 310 maize inbred lines using 186 polymorphic SSRs (Table S1).…”
Section: Germplasms Diversity and Multiple Insect-resistance Evaluationmentioning
confidence: 98%
“…When various groups (K value) ranging from 1 to 12 were compared, the ∆K reached the maximum value when K = 5, thus the 310 maize inbred lines were divided into five optimal groups (Figure 2A). The inbred lines with a membership probability of ≥0.500 were assigned to the same groups, and if the inbred lines had a membership probability of less than this value, they were assigned to a mixed group (not assigned to any of the five groups) [22,23]. Of the 310 inbred lines, 294 (accounting for 94.84%) were assigned to either one of the five groups, including the Lüda red cob (LRC; 44 lines) group, Tang si ping tou (TSPT; 81 lines) group, Lancaster (Lan; 52 lines) group, P (47 lines) group,…”
Section: Genetic Diversity and Population Structure Analysismentioning
confidence: 99%
“…Genetic diversity and genetic structure play pivotal roles in population genetic analyses (Ellis and Burke, 2007) and are essential components when assessing germplasm resources of various species. These aspects are crucial for evaluating genetic variation across populations and tracing the origins of species (Tsutsui et al, 2001;Geleta et al, 2006;Kolbe et al, 2007;Merceron et al, 2017;Islam et al, 2018;Slim et al, 2019;Zombardo et al, 2021;Kumar et al, 2022;Khan et al, 2023). Researchers leverage these insights to develop comprehensive conservation strategies tailored to safeguard and explore high-quality germplasm resources (Crozier, 2000;Pertoldi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For crop breeding and germplasm management, genome-wide single nucleotide polymorphisms that measure relatedness among distinct inbreds are highly useful [21]. However, SSR markers are also useful to identify the population structure and are considered suitable for association mapping since they are co-dominant, locus-specific, polymorphic, multi-allelic and highly repeatable [22,23]. By utilizing modern breeding tools, we can expedite the breeding process by identifying chromosomal locations and finding significant marker-trait associations through association mapping [24].…”
Section: Introductionmentioning
confidence: 99%